Hand Mycetoma: The Mycetoma Research Centre Experience and Literature Review. - Rowa Fathelrahman Omer; Nancy Seif El Din; Fadwa Awad Abdel Rahim; Ahmed Hassan Fahal (Public Library of Science (PLoS), 2016)
Mycetoma is a devastating, neglected tropical disease characterised by extensive tissue involvement resulting in destruction, deformities and disabilities in the affected patients. The hand is commonly affected by mycetoma thus compromises its functionality and hinder the patient's daily activities of living. In this communication, we report on 533 patients with hand mycetoma managed over a period of 24 years at the Mycetoma Research Centre, University of Khartoum, Khartoum, Sudan. Eumycetoma was the commonest type of mycetoma (83.3%) encountered. Males were predominately affected (69.2%) with a sex ratio of 2.2:1. The majority of the patients (84%) were young adult below the age of 40 years old at presentation. The generality of patients (86.4%) were from the Sudan mycetoma belt. Children and adolescents (28.1%), farmers (18.2%) and workers (17.4%) were more frequently affected. The majority of patients (67.4%) had disease duration of less than 5 years at presentation. The study, did not document significant history of local trauma, familial tendency, concomitant medical diseases or other predisposing cause for mycetoma in this population. Pain (23.1%) was not a disease feature in this series and 52% of patients had past surgery for mycetoma and recurrence. The right hand was affected most (60.4%), and 64% of them had small lesion at presentation. Conventional x-ray was only helpful in patients with advanced disease and the MRI accurately determined the disease extension. Cytological smears, surgical biopsies histopathological examination and grains culture were the principal diagnostic tools for causative organisms' identification. In the present series it was difficult to determine the treatment outcome due to high patients follow up dropout.